Universal message between Islam and Christianity: A comparative study between Muslim and Christian thinkers / Hani Ali A Albalawi - Hani Ali , A Albalawi (2017)
This study has sought to demonstrate the concept of universality linguistically and conventionally. It has also elaborated on the meaning of the term ‘universal message’ as well as discussed the meaning of Islam and Christianity. It has researched the concept of abolishment, and evidence of its occurrence in the previous religions. It has looked at the Muslims evidence of the universality of Islamic religion and acknowledgements from the religious books of people of the book, and the evidence of the seal of prophethood on it, and the nature of their relationship. The study traced the onset of the claim of Christianity’s universality, and discussed the Christians’ evidence on that and the role of Paul in the claim of the universality of Christianity. The two prominent thinkers of Islam referred to are: Jamal Sharqawi and Ahmed Hijazi Saqqa, while the two Christian thinkers are: Friz Samuel and Imad Hanna. The researcher addressed their evidences, opinions and points of agreement and disagreement, and the weights of their views. The study examined the characteristics of the universality of Islam and the world's need for a comprehensive universal message. The study answered the question about the real criterion for the distinction between the universality of Islam and the universality of Christianity. The study highlighted the raised suspicions about the universality of Islam, and has disproved them methodically and from a scientific perspective. The study relied on two research methodologies first inductive method by surveying all texts that shows the universality of the message then the analytical method by critical analysing of the texts that indicate the universality of Christianity and counter any suspicious opinion about Islam. The research reached important conclusions, most important among them is that the Jesus call was divine and monotheistic, but it did not remain unchanged. Rather, it was intercalated by other faiths. Paul had the major role in deviating Christianity from its true path. The texts that indicated the universality of Christianity were added and fabricated and were non-existent in the original scriptures as not as a single text in the Christian Gospels proved the universality of Christianity. The confirmed texts from the Quran and Sunnah proved the universality of Islam and the abolishment of previous religions. Also, the research highlights that arguments put forward by Islamic Thinkers are more stable and sound than the ones put forward by Christianity Thinkers. This research was motivated to contribute to the efforts in the field of comparative religion and Aqidah, in the hope of helping the truth seekers to reach the truth, and in an attempt to add a new to the studies related to Aqidah and Islamic Thought.